Plan de fortalecimiento para el desarrollo de la compañía Transscarvajal S.A cantón Guaranda, provincia Bolívar, período 2024-2028. - Acosta Carvajal, Cristhian Alexander (2024)
Transscarvajal S.A., a transportation company based in Ecuador, is embarking on a strategic strengthening process with the goal of becoming a benchmark in the sector during the 2024-2028 period. The Strengthening Plan, based on a rigorous methodology, will allow the company to identify its strengths, opportunities, and areas for improvement, taking as a basis the best practices of the sector and emerging trends. Through an in-depth diagnosis, an exhaustive bibliographic investigation, and an analysis of strategic alternatives, innovative strategies will be developed to strengthen the company, ensuring sustainable growth and a commitment to the communities it connects. Excellence in service, social responsibility, and the implementation of innovative practices will be the pillars of this process, consolidating Transscarvajal S.A. as a leader in the transportation sector in the region. This plan is not a final destination, but a starting point on a path to the top of success, where Transscarvajal S.A. will leave its indelible mark on the roads of Ecuador.